Factores de riesgo asociados a las secuelas post COVID 19 en pacientes adulto mayores, Hospital Básico Yaguachi noviembre 2023 – abril 2024 - Naranjo Masalema, Josefina Stefania (2024)
The present research study refers to the various risk factors associated with the consequences of post-COVID-19, in older adult patients at the Yaguachi Basic Hospital. Currently, thanks to various prevention methods, it has been possible to control the rate of infection of this virus, however, it is important to mention that the post-COVID complications that citizens manifest are a problem that has a direct impact on health, generating an imbalance in your lifestyle. Therefore, the development of this research will allow us to determine the incidence of these factors on the health of patients over 60 years of age. As a research methodology, the qualitative field method will be applied and to obtain the information necessary to resolve the present problem, the application of an interview was chosen. The main objective is to identify the most common risk factors associated with COVID-19.